1986
DOI: 10.1111/j.1365-2125.1986.tb05195.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salicylic and acetylsalicylic acid alone and in combination on platelet aggregation and prostanoid synthesis in man.

Abstract: The present study was designed to investigate the effects of salicylate on the antiplatelet action of acetylsalicylic acid as well as on in vivo prostanoid formation and platelet function in healthy volunteers. In the first study six female volunteers received 350 mg acetylsalicylic acid intravenously, with and without previous oral administration of sodium salicylate (1200 mg daily for 3 days). Urinary prostanoid excretion as well as platelet aggregation and thromboxane formation were measured before and duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 47 publications
(64 reference statements)
3
19
0
1
Order By: Relevance
“…As ASA acetylates cyclo-oxygenase irreversibly [7,8], and as its metabolite salicylic acid does not inhibit prostaglandin synthesis in oral doses up to 1.2 g t.i.d. [32], it can be inferred that the gradual recovery of PGE 2 excretion in our study reflects resynthesis of medullary cyclo-oxygenase.…”
Section: P<005supporting
confidence: 51%
“…As ASA acetylates cyclo-oxygenase irreversibly [7,8], and as its metabolite salicylic acid does not inhibit prostaglandin synthesis in oral doses up to 1.2 g t.i.d. [32], it can be inferred that the gradual recovery of PGE 2 excretion in our study reflects resynthesis of medullary cyclo-oxygenase.…”
Section: P<005supporting
confidence: 51%
“…Moreover, recently several cases have been documented in which these drugs were thought to cause acute renal failure (Kleinknecht et al, 1986). In vivo studies have shown that ASA reduces renal cyclooxygenase (Rosenkranz et al, 1986), however, the findings with paracetamol are controversial. In vitro paracetamol can cause inhibition of cyclooxygenase of sheep seminal vesicles (Flower, 1974) and in mice tissues (Brune & Peskar, 1980), albeit at relatively high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been well recognized that ASA inhibits cyclooxygenase in therapeutic concentrations in man (Rosenkranz et al, 1986), there is uncertainty concerning paracetamol. In vitro investigations have shown that paracetamol in concentrations of 5 mm inhibited rat renal medullary slice conversion of exogenous arachidonic acid to PGE2 (Mattamal et al, 1979;Zenser et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…However, observations dissociating the analgesic and the anti-inflammatory activities of non-opioids have also been reported. At analgesic doses, sodium salicylate does not inhibit urinary excretion of PGE 2 or PGI 2 metabolites in human volunteers [5]. Furthermore, though the COX inhibitory activities of salicylate and acetylsalicylic acid (ASA; aspirin) differs markedly [6], they show similar antiinflammatory potencies [7].…”
Section: Is Inhibition Of Prostaglandin Synthesis the Sole Mechanism mentioning
confidence: 99%